Clinical Outcome of Turkish Metastatic Breast Cancer Patients with Currently Available Treatment Modalities - Single Center Experience - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2014)
Background: Breast cancer is the most common malignancy and the second leading cause of cancer-related death among women in the developed countries. Despite advances in screening, improved local therapies and adjuvant systemic treatments, median survival of metastatic breast cancer patients (MBC) is in the range of 2-3 years at most. We aimed to investigate whether the prognostic factors and therapeutic responses of our Turkish patients are similar to those in the literature. Materials and Methods: We reviewed the medical records of MBC patients who had been treated in our institution between 1999-2009 and analyzed their clinicopathological features and survival outcomes retrospectively Results: A hundred and sixty patients were included. Median age was 47 (23-82), median follow up was 24 (2-186) months. At the time of diagnosis 59% of patients were under the age of 50 and 46% were postmenopausal. The majority (37%) had multiple sites of metastases. Forty percent received endocrine therapy and 40% chemotherapy as first line metastatic treatment. Thirty (20%) patients were treated with molecular targeting agents like trastuzumab, lapatinib and sunitinib, frequently combined with a chemotherapy agent. Five-year overall survival (OS) was 32% and median OS was 38 months for the whole group. Five year progression free survival (PFS) was 10% and median PFS was 10 months. Menopausal status, hormone receptor expression and disease free status had a significant impact on overall survival in the multivariate analysis (p 0.018, p 0.018 and p:0.003, respectively). Conclusions: All our patients were treated with the modern oncologic therapies recommended by the international guidelines. From our data, MBC patients live up to 3-4 years, indicating that further improvement beyond that requires development of new treatment modalities. The survival outcomes of our patients were consistent with the data reported in the literature.
Keywords: Metastatic breast cancer; chemotherapy; targeted therapy; survival outcomes; Turkey; TYROSINE KINASE INHIBITOR; FIRST-LINE THERAPY; PHASE-III TRIAL; POSTMENOPAUSAL WOMEN; 1ST-LINE THERAPY; AROMATASE INHIBITOR; ESTROGEN-RECEPTOR; CHEMOTHERAPY PLUS; HORMONE-THERAPY; HER-2 STATUS